Marinheiros em luta: a Revolta da Chibata e suas representações - Sousa, Cláudio Barbosa de (2012)
The theme of this dissertation (work paper) is the Revolta da Chibata, the uprising of sailors low ranking Navy of Brazil, broke out in November 1910 against corporal punishment, the long working hours and low wages, among other claims. The movement will be focused here on the assumption that there is a close relationship between the resistence of sailors and the general context of struggle for civil and social rights highlighting ways of coping with violent repression suffered by the poorest segment of the population restrained in their political participation in that period. This study was supported by a selection of materials comprising, in the press, journalistic and iconography texts, as well as the analysis of cultural productions, including music, theater and literary texts, adding monuments and celebrations gave way to attempts to building/destruction of the historical meaning of the Revolta da Chibata, target true battles around the memory of that event among constant process of redefinition and a lack of meaning.